IN VITRO ANTHELMINTIC ACTIVITY OF ABUTILON THEOPHRASTI MEDIK. (MALVACEAE) AGAINST EGGS AND L3 LARVAE OF HAEMONCHUS CONTORTUS - HASSAN, MUSHEERUL; RA, MIR; JOSHI, TRIPTI; AHMAD YATOO, FIRDOUS; HABIB, HUMA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was carried out to assess the in vitro anthelmintic activity of Abutilon theophrasti stem extracts. Methods: Simple maceration was employed for extraction. Solvents such as methanol, water, and hexane were used. Egg hatch test (EHT) and larval motility test were employed to check the anthelmintic activity of crude extracts. Concentrations of 500, 250, 125, 62.5, and 31.25 mg/ml were made. Levamisole and distilled water served as control, respectively. Results: All selected extracts displayed concentration-dependent inhibition except aqueous extracts. At higher concentration (500 mg/ml), stem extracts (methanol, aqueous, and ethanol) showed 74.39%, 72.5 and 70.03% of efficacy in EHT, respectively (p≤0.05). Meanwhile, inhibition of larval motility was seen higher with inhibition percentage of 79.79, 75.65, and 71.28 by methanolic, aqueous, and hexane extracts, respectively (p≤ 0.05). Conclusion: The presents study suggests active principles having anthelmintic efficacy in Abutilon theopharsti stem.